Integrating Ethnoscience in Project-Based Learning: Enhance Critical Thinking and Collaboration with Local Traditional Food (Journal of Science Learning, 2026)
Integrating ethnoscience into science learning provides a meaningful and culturally relevant learning experience for students. This study aims to investigate the effectiveness of Ethnoscience-Integrated Project-Based Learning (PjBL) using Cenil, a traditional Indonesian snack, in enhancing students' critical thinking and collaboration skills in science learning. The integration of ethnoscience is intended to create a culturally relevant and meaningful learning experience. The research employed a quasi-experimental design with a pre-test and post-test control group. Participants were eighth-grade students from a junior high school in Magelang, Indonesia, selected through convenience sampling. The experimental group was taught using Ethnoscience-Integrated PjBL, while the control group received Direct Instruction. Data were gathered through critical thinking and collaboration assessments, observation sheets, and peer evaluations. Multivariate Analysis of Variance (MANOVA) and effect size (partial eta squared) were used for analysis. The results demonstrated a statistically significant improvement in the experimental group’s critical thinking and collaboration skills compared to the control group (p 0.05, partial eta squared = 0.996). Students in the experimental group showed better performance in analyzing scientific problems, proposing solutions, and engaging in teamwork throughout the learning project. The integration of ethnoscience into PjBL, particularly through the context of traditional food, enhances students' critical thinking and collaborative abilities. This study highlights the potential of combining cultural knowledge with innovative learning strategies to bridge scientific understanding and local wisdom. The findings support the incorporation of ethnoscience into science education as an effective means to promote higher-order thinking and social interaction in real-world contexts.